Facile preparation of a thermosensitive and antibiofouling physically crosslinked hydrogel/powder for wound healing. Issue 13 (15th March 2022) - Dong, Xiaoru; Yao, Fanglian; Jiang, Lijie; Liang, Lei; Sun, Hong; He, Shaoshuai; Shi, Mingyue; Guo, Zhicheng; Yu, Qingyu; Yao, Mengmeng; Che, Pengcheng; Zhang, Hong; et al.
Abstract : In this paper, a full physically crosslinked HBC-PSB hydrogel with multiple functions was prepared by a facile method and can effectively prevent postoperative abdominal adhesion and accelerate the healing of infected wounds. Abstract : To improve the therapeutic effect of a hydrogel on damaged tissue, a series of hydroxybutyl chitosan (HBC) and poly(sulfobetaine methacrylate) (PSBMA) composite hydrogels (HBC-PSB) with thermosensitivity, self-healing, antibiofouling, and synergistic antibacterial activity are prepared by mechanical blending. The electrostatic interaction among PSBMA and hydrophobic association among HBC are the main drive force to form a full physically crosslinked hydrogel. HBC can avoid the aggregation and precipitation of PSBMA caused by intermolecular strong association. Meanwhile, the existence of the PSBMA network can promote the sol–gel transition of HBC. Due to the reversible physical crosslinking, the HBC-PSB hydrogel shows excellent self-healing behaviors, and can be stored as dry powder. Intriguingly, the composite hydrogel has good synergistic antibacterial performance via the anti-protein adhesion ability of the PSBMA network and bactericidal ability of the HBC network. Based on these results, a sidewall defect–cecum abrasion model and an infected full-thickness skin defect model are used to investigate the application of the prepared HBC-PSB hydrogel in postoperative anti-adhesion and healing of infected wounds, respectively. The results suggest that the HBC-PSB hydrogel can completely cover the irregular damaged tissue surface, moreover, it can effectively decrease the formation of postoperative adhesion and improve the healing speed of infected wounds via reducing the adhesion and growth of bacteria. Overall, we propose that the HBC-PSB hydrogel is a promising candidate in biomedical applications.